PRAKTEK IMPRESSION MANAGEMENT PADA UMKM DI INDONESIA - Vivi Kumalasari Subroto; Eni Endaryati; Setiawan Setiawan (MANAJEMEN, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive business entities owned by individuals who have a role and contribution to the Indonesian economy. The presence of MSMEs greatly supports the national economy. Internally, the MSME sector needs to empower employees and build a better management system to maintain its business image. On the other hand, problems related to branding also often occur among MSMEs, these two problems faced by MSMEs can be solved by implementing an image management strategy. One of the motivations for implementing this strategy is how they want to influence and benefit others [13]. Baktik's research [5] proves the influence of impression management on employee productivity at Chocolicious Indonesia Stores. On the other hand, according to dramaturgical theory, the use of digital branding and marketing techniques in MSMEs is part of the front stage. This concept is supported by Prabhawati's findings [10] that brand image has a higher influence on purchasing decisions for MSME products assisted by Jogja Sukurmi Key words: impression management, dramaturgi theory, MSMEs